THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL SELF-EFFICACY, AND SOCIAL NORMS ON RISK CREDIT BEHAVIOR IN PAYLATER USERS - Islamiyah, Maya Adillah; Widodo, Heri (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study was conducted with the aim of determining whether Objective Financial Literacy, Subjective Financial Literacy, Financial Self-Efficacy and Social Norms have an effect on Risky Credit Behavior in the use of the Paylater feature. Method: This type of research uses associative with a quantitative approach. In this study, the population used was all students of the Accounting study program at the University of Muhammadiyah Sidoarjo and a sample of 100 students using the Paylater feature was obtained. The data in this study used primary data collected through a survey questionnaire. The data collection technique used a Likert scale derived from variable indicators using data analysis techniques using SPSS 23 Software. Results: The results of this study indicate that there is a negative and significant influence on Objective Financial Literacy and Subjective Financial Literacy while Financial Self-Efficacy and Social Norms show a positive and significant influence on Risky Credit Behavior in the use of the Paylater feature. Novelty: This study offers a new contribution by simultaneously analyzing the influence of Objective Financial Literacy, Subjective Financial Literacy, Financial Self-Efficacy, and Social Norms on Risky Credit Behavior in the context of Paylater usage among university students—a topic that remains underexplored in previous literature, particularly among young users of digital financial services.